Tecnologias em fertilizantes fosfatados no cultivo da batata para processamento industrial - Andrade, Bruno Bernardes de (2021)
Potatoes are grown in virtually every country in the world. It is deemed to be of great importance in human nutrition, not only because of its energetic composition but also because it is a source of mineral salts. It is part of the human diet, whether fresh or processed (pre-cooked and in chips). Potato growing is a high-investment activity. Spending on fertilizers is among the highest, especially with regard to phosphorus, given its great demand. Thus, this study evaluated the development and yield of potatoes for industrial processing submitted to fertilization with phosphate fertilizers of different technologies (organomineral, conventional, and polymerized fertilizers). In the winter of 2017, at Água Santa Farm, located in the municipality of Perdizes – Minas Gerais, two potato varieties (Markies and “Codified”) were cultivated in two simultaneous experiments using DBC with 12 phosphate fertilizers and 650 kg ha-1 of P2O5 at planting. Cover fertilization (N and K) was carried out in the heap operation approximately 28 days after planting, comparing the dose of these nutrients to that provided at planting when using N-P-K fertilizers. In the winter of 2018, an experiment was conducted at this same property with the planting of the cultivar "Markies" in DBC in a factorial scheme (4x4+1), using P2O5 (0, 300, 400, 500, and 600 kg ha-1) and phosphate fertilizers with different technologies (MAP, FOM, NPK 04-30-04, NPK 05-30-04). In the heap, cover fertilization was done with N and K, equating their amounts to that promoted with the greatest supply of these nutrients with the N-P-K fertilization at planting. The following characteristics were evaluated: yield, number of tubers, classification of tubers according to size, total soluble solids, and leaf and residual phosphorus content in the soil. The results were analyzed through ANOVA and the means were compared using the Scott-Knott test and adjusted regression models. An increase in yield was observed with the application of phosphate fertilizers in relation to the treatment in which there was no addition of P; the maximum yield was obtained with the use of MAP (55.11 t ha-1). This fertilizer also stood out positively in the number of tubers classified as large (228 units) for the “Markies” variety. The content of total soluble solids was influenced by the use of P in the management of fertilization, and the fertilizers tested did not differ from each other. The residual P content in the soil was higher when some fertilizers were applied, compared to the control treatment. The interaction between fertilizers and the amount of P2O5 was not significant; quadratically, there was an isolated effect only of the amount of P2O5 on the yield of tubers, with the amount of 516.99 kg ha-1 of P2O5, which triggered maximum yield as well as increasing linear behavior in leaf P content. In areas with high levels of phosphorus, the association of technologies with phosphate fertilizers did not increase the agronomic efficiency in the cultivation of potatoes for industrial processing compared to conventional fertilizers.